2009
DOI: 10.1021/ct9005322
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of Catalytic Zinc Coordination in Thermolysin and HDAC8: A Born−Oppenheimer ab Initio QM/MM Molecular Dynamics Study

Abstract: AbstracsThe different coordination modes and fast ligand exchange of zinc coordination has been suggested to be one key catalytic feature of the zinc ion which makes it an invaluable metal in biological catalysis. However, partly due to the well known difficulties for zinc to be characterized by spectroscopy methods, evidence for dynamic nature of the catalytic zinc coordination has so far mainly been indirect. In this work, Born-Oppenheimer ab initio QM/MM molecular dynamics simulation has been employed, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 68 publications
(155 reference statements)
2
94
0
Order By: Relevance
“…This cleavage site of Aβ peptide by S. aurantiaca ACE is in good agreement with the previous experimental and computational studies of Aβ peptide degradation by human ACE [Hu et al, 2001;Jalkute et al, 2013;Oba et al, 2005]. These results may be compared with earlier metalloprotease studies [Fernandez et al, 2001;Manzetti et al, 2003;Matthews, 1988;Wu et al, 2009]. In summary, microbial enzymes could be useful to understand Aβ degradation in detail at the atomic level.…”
Section: Proposed Cleavage Mechanism Of Aβ Peptidesupporting
confidence: 90%
“…This cleavage site of Aβ peptide by S. aurantiaca ACE is in good agreement with the previous experimental and computational studies of Aβ peptide degradation by human ACE [Hu et al, 2001;Jalkute et al, 2013;Oba et al, 2005]. These results may be compared with earlier metalloprotease studies [Fernandez et al, 2001;Manzetti et al, 2003;Matthews, 1988;Wu et al, 2009]. In summary, microbial enzymes could be useful to understand Aβ degradation in detail at the atomic level.…”
Section: Proposed Cleavage Mechanism Of Aβ Peptidesupporting
confidence: 90%
“…For example, Quantum Mechanical (QM) methods, [5][6] Molecular Mechanical (MM) methods [7][8][9] and combined QM/MM methods. [10][11] For MM methods, there are a number of strategies that have been employed: the bonded model, 8,[12][13][14][15] the nonbonded model, 9,[16][17][18][19][20] the hybrid model, 21 the cationic dummy model, 7,[22][23] the constrained nonbonded model, 24 the pointson-a-surface model 25 and the polarizable model [26][27][28] all have been described and parameterized to study a broad range of metal containing complexes. The 12-6 LennardJones (LJ) nonbonded model is widely used due to its simple form, ease to parameterize, speed advantage and excellent transferability.…”
Section: Introductionmentioning
confidence: 99%
“…This method can take the polarizable electrostatic effect into account explicitly and accurately treat hydrogen bonding interactions. For instance, Wu et al applied Born-Oppenheimer DFT QM/MM MD simulations to study the impact of the linker component on histone deacetylase inhibition specificity and they found that the chelation mode of hydoxamate with the zinc ion in HDAC is modulated by water accessing to the linker binding channel (Wu, Hu et al, 2009). Wu et al performed semi-empirical QM/MM MD simulations with the semi-empirical parameterized model 3 (PM3) (Stewart, 1989) on acutolysin A complex to probe the fourth ligand of zinc in acutolysin A, and their results showed that the fourth ligand in the active site of the reported X-ray crystal structure is a water molecule rather than a hydroxide anion (Wu, Wong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%